COMMUNITY EMPOWERMENT THROUGH ORGANIC VEGETABLE CULTIVATION AND CATFISH IN BUCKETS AND ITS PROCESSED DIVERSIFICATION - Muhammad Syahril; Ainul Mardiyah; Hanisah Hanisah; Dolly Sojuangan Siregar (LPPM dan PM Universitas Samudra, 2022)
Organic farming is an agricultural cultivation technique that relies on natural ingredients without the use of synthetic chemicals. The cultivation technology focuses on environmental sustainability and sustainable environmental insights. Community service based on organic farming can be carried out in Paya Bujok Tunong Village with 144 farming households, 53 of which are horticultural farming businesses. The methods used in this service are: (1) Socializing the importance of using yards during the Covid-19 pandemic; (2) Transferring knowledge related to organic plant and catfish cultivation technology in yards; (3) Processing organic agricultural products so that they have more economic value; (4) Carry out mentoring activities during the implementation of activities; and, (5) evaluate activities. PKK women in Paya Bujok Tunong Village through PKM Unsam activities can be empowered by utilizing the yard by planting organic vegetables and organic catfish. To optimize revenue, diversification of processed yields into onion cakes and catfish meatballs was also carried out, as well as assistance and donations to various supporting facilities and infrastructure.